Isolation and characterization of a molybdenum-reducing and SDS- degrading Klebsiella oxytoca strain Aft-7 and its bioremediation application in the environment - Masdor N.; Abd Shukor M.S.; Khan A.; Bin Halmi M.I.E.; Abdullah S.R.S.; Shamaan N.A.; Shukor M.Y. (Society for Indonesian Biodiversity, 2024)
Indexed by Scopus